An Analytical Overview of US-India Relations - Dr. Iram Khalid (Journal of Political Studies, 2009)
The rapidly changing international world scenario demands more time to move on dealing with economic and security challenges. In this perspective, the purpose of this article is to take an analytical overview of two strategic partners’ relations, India and the United States of America. These both countries have their own specific agendas to pursue their interests. The diplomatic events in the Indian foreign policy proved that the Indian political leadership focused on tactical relations with the international community in the pursuing of national interests. Profiled responsible institutional attitude placed India to play a vital and meaningful role in the regional and international politics. That is why the ‘123Agreement’ opened a new dimension of US India relations to avail new challenges and opportunities. Again the revival of the New Great Game in Central Asian region forced India to understand the US presence in Afghanistan as tactfully and strategically. Irrespective of common clashes and interest, it is observed that Washington showed serious reservations to those steps, which can encircle to economic and strategic benefits of Indians.